Chứng Minh : (x+y) ³ + 3(x+y) ²(x-y) + 3(x+y)(x-y) ² + (x-y) ³ = 8x ³

Chứng Minh : (x+y) ³ + 3(x+y) ²(x-y) + 3(x+y)(x-y) ² + (x-y) ³ = 8x ³

2 bình luận về “Chứng Minh : (x+y) ³ + 3(x+y) ²(x-y) + 3(x+y)(x-y) ² + (x-y) ³ = 8x ³”

  1. Biến đổi vế trái:
    (x+y)^³+3(x+y)^²(x-y)+3(x+y)(x-y)^²+(x-y)^³
    =(x+y+x-y)^3
    =(2x)^3
    Ta có vế phải:
    8x^3=(2x)^3
    Mà (2x)^3=(2x)^3
    => VT=VP (đpcm)
    $\color{red}{\text{@Hy~Hoctotnha}}$
     

    Trả lời
  2. Giải đáp + Lời giải và giải thích chi tiết:
    (x + y)^3 + 3(x + y)^2(x – y) + 3(x + y)(x – y)^2 + (x – y)^3 = 8x^3
    VT = (x + y)^3 + 3(x + y)^2(x – y) + 3(x + y)(x – y)^2 + (x – y)^3
         = [(x + y) + (x – y)]^3
         = (x + y + x – y)^3
         = (2x)^3
         = 8x^3 = VP (đpcm).

    Trả lời

Viết một bình luận

Câu hỏi mới